Sickle red cells as danger signals on proinflammatory gene expression, leukotriene B4 and interleukin-1 beta production in peripheral blood mononuclear cell. (July 2016) - Pitanga, Thassila N.; Oliveira, Ricardo R.; Zanette, Dalila L.; Guarda, Caroline C.; Santiago, Rayra P.; Santana, Sanzio S.; Nascimento, Valma M.L.; Lima, Jonilson B.; Carvalho, Graziele Q.; Maffili, Vitor V.; Carvalho, Magda O.S.; Alcântara, Luiz C.J.; et al.
Highlights: SCA patients have inflammatory mediator's levels higher than in healthy controls. RBC from SCA patients induce TLR and NLRP3 inflammasome expression. HU does not prevent NLRP3 inflammasome- and TLR-dependent inflammation. TLR and NLRP3 pathways may be key inducers for inflammation in SCA. Abstract: This study tested the hypothesis that sickle red blood cell (SS-RBC) induce Toll-like receptors (TLR) and Nod-like receptor family, pyrin domain containing 3 (NLRP3)- inflammasome expression in peripheral blood mononuclear cells (PBMC). TLR and NLRP3 inflammasome could contribute to the maintenance of the inflammatory status in sickle cell anemia (SCA) patients, since SS-RBC act as danger signals activating these pathways. In this study, first, we evaluated TLR (2, 4, 5 and 9), NLRP3, Caspase-1, interleukin (IL)-1β and IL-18 expression in PBMC freshly isolated from SCA patients (SS-PBMC) in comparison with PBMC from healthy individuals (AA-PBMC). In the second moment, we investigated whether SS-RBC could interfere with the expression of these molecules in PBMC from healthy donor, in the absence or presence of hydroxyurea (HU) in vitro. TLRs and NLRP3 inflammasome expression were investigated by qPCR. IL-1β, Leukotriene-B4 (LTB4 ) and nitrite production were measured in PBMC (from healthy donor) culture supernatants. TLR2, TLR4, TLR5, NLRP3 and IL-1β were highly expressed in SS-PBMC when compared to AA-PBMC. Additionally, SS-RBC induced TLR9, NLRP3, Caspase-1, IL-1β and IL-18 expression and induced IL-1β, LTB4 and nitrite production in PBMC cultures. HU did not prevent TLR and NLRP3 inflammasome expression, but increased TLR2 and IL-18 expression and reduced nitrite production. In conclusion, our data suggest that TLR and inflammasome complexes may be key inducers of inflammation in SCA patients, probably through SS-RBC; also, HU does not prevent NLRP3 inflammasome- and TLR-dependent inflammation, indicating the need to develop new therapeutic strategies to SCA patients that act with different mechanisms of those observed for HU.